Recent Progress of Mycotoxin in Various Food Products—Human Exposure and Health Risk Assessment - Kailin Li; Hua Cai; Baozhang Luo; Shenggang Duan; Jingjin Yang; Nan Zhang; Yi He; Aibo Wu; Hong Liu (Foods)
Mycotoxins, as prevalent contaminants in the food chain, exhibit diverse toxicological effects on both animals and humans. Chronic dietary exposure to mycotoxin-contaminated foods may result in the bioaccumulation of these toxins, posing substantial public health risks. This review systematically examines the contamination patterns of mycotoxins across major food categories, including cereals and related products, animal-derived foods, fruits, and medical food materials. Furthermore, we critically evaluated two methodological frameworks for assessing mycotoxin exposure risks: (1) dietary exposure models integrating contamination levels and consumption data and (2) human biomonitoring approaches quantifying mycotoxin biomarkers in biological samples. A key contribution lies in the stratified analysis of exposure disparities among population subgroups (adults, teenagers, children, and infants). Additionally, we summarize current research on the relationship between human mycotoxin biomonitoring and associated health impacts, with a particular emphasis on vulnerable groups such as pregnant women and infants. By elucidating the challenges inherent in existing studies, this synthesis provides a roadmap for advancing risk characterization and evidence-based food safety interventions.